Biochemical Characterization of a Novel Endo-1,3-β-Glucanase from the Scallop Chlamys farreri - Zhijian Li (Marine Drugs, 2020)
Endo-1,3-β-glucanases derived from marine mollusks have attracted much attention in recent years because of their unique transglycosylation activity. In this study, a novel endo-1,3-β-glucanase from the scallop Chlamys farreri, named Lcf, was biochemically characterized. Unlike in earlier studies on marine mollusk endo-1,3-β-glucanases, Lcf was expressed in vitro first. Enzymatic analysis demonstrated that Lcf preferred to hydrolyze laminarihexaose than to hydrolyze laminarin. Furthermore, Lcf was capable of catalyzing transglycosylation reactions with different kinds of glycosyl acceptors. More interestingly, the transglycosylation specificity of Lcf was different from that of other marine mollusk endo-1,3-β-glucanases, although they share a high sequence identity. This study enhanced our understanding of the diverse enzymatic specificities of marine mollusk endo-1,3-β-glucanases, which facilitated development of a unique endo-1,3-β-glucanase tool in the synthesis of novel glycosides.